Linkages between pro-poor growth, social programmes and labour market: The recent Brazilian experience - Nanak Kakwani; Marcelo Neri; Hyun H. Son (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper analyses the relationship between growth patterns, poverty, and inequality in Brazil during its globalization process, focusing on the role played by the labour market and social programmes. Methodologically, the paper makes two contributions to the literature. One is the proposal of a new measure of pro-poor growth, which links growth rates in mean income and in income inequality. The other contribution is a decomposition methodology that explores linkages between three dimensions: growth patterns, labour market performances, and social policies. The proposed methodologies are then applied to the Brazilian National Household Survey covering the period 1995-2004.
Keywords: D31; I32; N36; O15; J21; I38; 330; inequality; poverty; growth; pro-poor growth; labour market; social policy; Armut; Einkommensverteilung; Wirtschaftswachstum; Sozialpolitik; Arbeitsmarkt; Brasilien